Community process: community education's promise - William M. Hetrick (Educational Considerations, 1977)
The year Nineteen Seventy-six promises to be the most exciting year in our nation's history, as cities and hamlets of varying sizes across the United States prepare to celebrate the 200th birthday of the greatest democracy in the world.